DOMINANSI, KEKAYAAN DAN KEMERATAAN JENIS VEGETASI HUTAN PANTAI TINGKAT PERMUDAAN DI KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Komul, Yulianus Dominggus; Sahupala, Andjela; Siahaya, Troice Elsye; Sahupala, George Loudewik (JURNAL HUTAN LESTARI, 2024)
Coastal forest vegetation on sandy and rocky soil above the coastline. Its presence is scattered along the coastline with different variations according to the coastal topography. The existence of the coastal forest in the coastal village of Kairatu with its vegetation also makes a difference to the species and types contained therein. This study aims to analyze the value of dominance, richness and evenness of tree species at the growth rate of youth spread along the coastline of Hatusua, Waipirit and Kairatu Villages in Kairatu District, West Seram Regency. Survey Method Continuous Line Plot sampling is applied to obtain data, with the length of the line adjusted to the length of the long line. Based on the results of analysis of research data on vegetation at the regeneration level (Seedlings, Saplings and Poles) the value of the species dominance index (C) was obtained between 0.0148 "“ 0.2265. Species richness index (R1) values range from 0.0148 to 0.2759 and species evenness index values (E) range from 0.0309 to 0.0669. Thus it can be concluded that the values of the three categories studied are in the low criteria because they do not exceed the minimum threshold value of the specified index value provisions.Keywords: Coastal Forest Vegetation Analysis, Youth Level, Kairatu District.Abstrak  Vegetasi hutan pantai yang berada pada tanah berpasir dan berbatu dibagian atas garis pantai. Keberadaannya tersebar disepanjang garis pantai dengan keragaman yang berbeda sesuai dengan topografi pantai. Keberadaan hutan pantai pesisir desa kairatu dengan vegetasi yang dimilikinya turut memberikan perbedaan terhadap spesies dan jenis yang terkandung didalamnya. Penelitian ini bertujuan menganalisis nilai dominansi, Kekayaan serta Kemerataan Jenis pohon pada tingkat pertumbuhan permudaan yang tersebar sepanjang garis pantai Desa Hatusua, Waipirit dan Kairatu di Kecamatan Kairatu Kabupaten Seram Bagian Barat. Metode Survei Continyu Line Plot sampling diterapkan untuk memperoleh data, dengan panjang jalur disesuaikan dengan panjang garis panjang. Berdasarkan hasil analisis data penelitian vegetasi tingkat permudaan (Semai, Pancang dan Tiang) diperoleh nilai indeks dominansi jenis (C) berkisar anatara 0,0148 "“ 0,2265. Nilai Indeks kekayaan jenis (R1) berkisar 0,0148 "“ 0,2759 dan nilai Indeks Kemerataan jenis (E) berkisar 0,0309 "“ 0,0669 . dengan demikian dapat disimpulkan bahwa nilai ketiga kategori yang diteliti berada pada kriteria rendah karena tidak melampaui nilai ambang minimal dari ketentuan nilai indeks yang ditentukan.   Kata Kunci : Analisis Vegetasi Hutan Pantai, Kecamatan Kairatu.